PERAN PENDIDIKAN EKONOMI DALAM MENINGKATKAN BUDAYA KEWIRAUSAHAAN DAN MENYIKAPI PERDAGANGAN BEBAS - Muhammad Rakib, (Pendidikan Ekonomi, 2010)
Economic education is expected to set alumnae to have competitiveness and entrepreneural culture. Along with economic globalization, the borders of countries blur and the relation of national economy and international economy is getting tighter. In one hand, globalization in economy will increase the competitiveness of domestic products. On the other hand, globalization opens the possibility of global products to enter the domestic market. In fact, national economy is part of global economy. Thus, as a citizen we have to compete with other countries in order not to be expelled from the tight competition in the free trade era.